Sifat Sensori dan Karakteristik Fisik Tortila Jagung - Zukryandry; Muslihudin; Annisa Fitri (LPPM Universitas Terbuka, 2022)
Corn (Zea mays) is a food crop that has economic value and development potential because it is the most important source of carbohydrates and protein after rice. Utilization of corn can be expanded by making corn flour which is then processed into tortila products. This study aims to determine the appropriate formulation of cassava starch for the sensory and physical properties of corn tortilas. The research design used was a factorial design with 4 additional treatments of cassava starch (0%, 5 %, 10 %, and 15 %) and 3 repetitions. Tests performed are the hedonic test (color, taste, aroma and texture) and physical test (hardness test and the swelling volume) of the tortila products produced. Cassava flour formulation of 15% has the most likability factor with the subjects according to their texture. Cassava starch formulations in tortilas show an increase in hardness value of 0,50 kg/cm2 (0%), 0,52 kg/cm2 (5%), 0,53 kg/cm2 (10%) dan 0,54 kg/cm2 (15%). Corn tortilas with tapioca formulation affect the percentage of swelling volume, the greater the percentage of cassava starch, the greater the highest volume of corn tortila with the swelling percentage of 153% (0%) to 217% (15%).